Effects of Renal Impairment and Hemodialysis on the Pharmacokinetics and Safety of the Glecaprevir and Pibrentasvir Combination in Hepatitis C Virus-Negative Subjects - Kosloski, Matthew P.; Zhao, Weihan; Marbury, Thomas C.; Preston, Richard A.; Collins, Michael G.; Pugatch, David; Mensa, Federico; Kort, Jens; Liu, Wei (Antimicrobial agents and chemotherapy, 2018)
Hepatitis C virus (HCV) infection is an independent risk factor for developing chronic renal impairment and end-stage renal disease. Limited treatment options are available for HCV genotype 2, 3, 5, and 6 infections in patients with an estimated glomerular filtration rate (eGFR) of <30 ml/min. Glecaprevir and pibrentasvir are active against all six major HCV genotypes, are primarily excreted in the bile, and have minimal renal elimination. Therefore, combined treatment with these direct-acting antivirals may be useful for patients with HCV infection and chronic kidney disease. A phase 1, multicenter, open-label study evaluated the effects of renal impairment on the pharmacokinetics and safety of glecaprevir-pibrentasvir. In substudy 1, 38 subjects with stage 2 to 5 chronic kidney disease who were not on dialysis or who had normal renal function received single doses of the combination of 300 mg glecaprevir and 120 mg pibrentasvir. In substudy 2, 8 subjects requiring hemodialysis received single doses of the combination of 300 mg glecaprevir and 120 mg pibrentasvir under dialysis and nondialysis conditions. Regression analyses demonstrated increased glecaprevir and pibrentasvir plasma exposures, as determined by the area under the curve, with decreasing renal function, up to 56% and 46%, respectively, in subjects with an eGFR of <15 ml/min/1.73 m 2 . In dialysis-dependent subjects, glecaprevir and pibrentasvir exposures were similar (≤18% difference) when study drugs were administered before hemodialysis or on a nondialysis day. Adverse events were mostly mild, with the most common being self-limited fatigue (3 subjects). The study findings support the clinical evaluation of glecaprevir-pibrentasvir without dose adjustment in HCV-infected subjects with renal impairment. (This study has been registered at ClinicalTrials.gov under registration number NCT02442258.)